Comparative study of laparoscopic versus open surgery in cases of liver hydatid cysts - Padmane Sagar Gajanan; Ajay Patidar; Ashish Pratap Singh; Priyank Sharma (Asian Journal of Medical Sciences, 2023)
Background: Hydatidosis is a zoonotic infection, and treatment is mandatory to avoid complications. The infection can be asymptomatic or severe, causing extensive organ damage and even death of the patient. Aims and Objectives: The main aim of this study is to find out the merits and demerits of laparoscopy over that of open surgery in the treatment of hydatid cysts of liver. Materials and Methods: This prospective observational study was done on 50 patients who had liver hydatid disease admitted in the Department of Surgery, Shyam Shah Medical College Rewa (M.P.). Patients were divided into two groups consisting of 25 cases in each. Group A: managed by laparoscopic surgery and Group B: managed by open surgery. Results: The mean operative time in Group A was 99.6 min, while in Group B, it was 140.4 min. Group A patients were mobilized early and resumed duty very fast then Group B. The mean duration of stay in hospital was 8.64 days (range: 4–20 days) in Group A and 11.84 days (range: 4–12 days) in Group B. Wound infection seen in 9 patients in Group B and 0% in Group A. General complication rate was 32% in Group B and 8% in Group A. No recurrence noticed in either group during follow-up. Conclusion: Overall laparoscopic management of liver hydatid cyst is cost-effective in terms of early mobilization, early discharge, and early resumption of work along with cosmetic benefit.